Immunoglobulin M oligoclonal bands: Biomarker of targetable inflammation in primary progressive multiple sclerosis. Issue 2 (2nd July 2014) - Villar, Luisa M.; Casanova, Bonaventura; Ouamara, Nadia; Comabella, Manuel; Jalili, Farzaneh; Leppert, David; de Andrés, Clara; Izquierdo, Guillermo; Arroyo, Rafael; Avşar, Timuçin; Lapin, Sergey V.; Johnson, Trina; et al.
<x xml:space="preserve">Abstract</x> Objective To identify a biomarker distinguishing patients who, despite a primary progressive multiple sclerosis (PPMS) clinical course, may nonetheless benefit from immune therapy. Methods The presence or absence of both immunoglobulin (Ig) G and IgM oligoclonal bands (OCB) was blindly examined in paired cerebrospinal fluid (CSF) and serum samples from a large PPMS patient cohort, and related to clinical and imaging evidence of focal inflammatory disease activity. Results Using both cross‐sectional samples and serial sampling in a subgroup of patients followed prospectively as part of the placebo‐controlled OLYMPUS study of rituximab in PPMS, we found that the presence of CSF‐restricted IgM OCB (but not of IgG OCB) is associated with an active inflammatory disease phenotype in PPMS patients. This finding was confirmed in an independent, multicenter validation cohort. Interpretation The presence of CSF IgM OCB may be a biomarker for a subset of PPMS patients with more active inflammatory disease, who may benefit from immune‐directed treatments. Ann Neurol 2014;76:231–240